1993
DOI: 10.1002/j.1834-4461.1993.tb02428.x
|View full text |Cite
|
Sign up to set email alerts
|

The Great Shoe Store Robbery1

Abstract: This article contributes to the significant debate on the effects of the Australian criminal justice system on Aborigines and in particular Aboriginal youth. This debate fed into nation‐wide concern over an ever increasing number of Aboriginal deaths in custody, recently culminating in the Federal Royal Commission into Aboriginal Deaths in Custody. Through the use of case studies and other ethnographic data drawn from investigations in the country town of Port Augusta, South Australia, the author illustrates h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Additionally, several commentators (e.g. Hutchings, 1993;Tyler, 1998) have suggested that the commission of these crimes by Australian aborigines may be governed by sociocultural and other considerations that are not typically observed in the non-Aborigine population. In many Australian rural towns, for example, disadvantaged Aborigines live on the fringe of the town and therefore might be expected to show a commuter offence pattern more commonly than do other Australian burglars.…”
mentioning
confidence: 99%
“…Additionally, several commentators (e.g. Hutchings, 1993;Tyler, 1998) have suggested that the commission of these crimes by Australian aborigines may be governed by sociocultural and other considerations that are not typically observed in the non-Aborigine population. In many Australian rural towns, for example, disadvantaged Aborigines live on the fringe of the town and therefore might be expected to show a commuter offence pattern more commonly than do other Australian burglars.…”
mentioning
confidence: 99%
“…Their futility, as they increase the levels of state surveillance over the young people and reincorporate them into the folds of the legal-welfare structures they resist, becomes apparent to the young people whose attempts at agency exact a heavy toll and (at least in this case) attempt to generate legitimate means to refute state control (Hutchings, 1993: The panoptic ways of imposing disciplinary norms over deviant populations proliferate beyond the punitive and repressive police gaze described earlier and, for the young people, not all the attention attracted by their outrageous behaviour is negative. A host of 'caring' agencies surveil the park daily, providing a wide range of health and welfare services.…”
Section: Sluggin' It Out: the Panopticon's Failure And Subsequent Reamentioning
confidence: 96%
“…In the 1980s younger anthropologists began to follow Beckett () by recording rural southern Aborigines’ lively responses and commentary on their stigmatised identities, revealing perceptive, satirical anti‐colonial practices (Morris , ; Carter ; Cowlishaw ; Hutchings ). But such ethnographies are not common.…”
Section: Wedged Between Historians and Aboriginal Authoritymentioning
confidence: 99%